Optimal Tilt Angle of Photovoltaic Panels: A Case Study in the City of Rio de Janeiro - Gomes, Alexandro; Oliveira, Maria Francisca do Nascimento; Musci, Marcelo (Environmental Management and Sustainable Development, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The optimal tilt angle of photovoltaic panels plays a crucial role in energy generation. However, the accumulation of dust on solar panels can significantly impact their performance and efficiency, leading to a reduction in energy production. Therefore, it is crucial to consider the effect of dust deposition on the optimal tilt angle of solar panels. Regarding panel installation, it is often observed that panels are positioned to follow the natural slope of the roofs, disregarding the optimal angle for maximizing solar radiation utilization. Numerous studies have investigated the impact of dust accumulation on the performance of photovoltaic panels and the optimal inclination angle for different regions and seasons. This study aims to analyze the optimal tilt angle of photovoltaic panels for maximum energy generation, considering undesired effects such as dust, dirt, water droplets, and other atmospheric factors. The authors have proposed an equation to calculate the optimal tilt angle of photovoltaic panels based on a case study conducted in different Rio de Janeiro City regions. The methodology employed in this study involves estimating solar incidence on the surface of the photovoltaic panels using the authors’ proposed equation, which considers the latitude and longitude of the panel installation location. The results obtained were validated using software that generates hourly solar radiation data. The results indicate that an inclination of 30 degrees, calculated using the proposed equation, resulted in a 2% deviation from the optimal theoretical angle.